English language assessment in Malaysia: teachers’ practices in test preparation - Looi-Chin , Ch’ng; Rethinasamy, Soubakeavathi (Issues in Language Studies, 2013)
In the context of English language teaching, many studies that claimed to investigate teachers’ assessment practices were actually exploring their perceptions and belief with little reference to what they were practising in schools. The need to address such a limitation has prompted this study to examine the current formal assessment practices of English language teachers in lower secondary schools. Specifically, this paper reports how the teachers prepare the formal assessments. Extensive structured interviews were conducted with 72 teachers from 24 schools in Kuching division, Sarawak. Relevant documents such as test papers and assessment guidelines were also collected for further analysis. The findings from this study revealed that a majority of the teachers conducted formal assessments mainly due to the requirements of the school and ministry while following pre-determined steps in preparing a test. Furthermore, the findings also revealed teachers’ reliance on commercial reference books in constructing exam questions and sample answers. The outcome of the study provides an insight on the nature of English language teachers’ assessment practices in relation to the classroom teaching and learning at the secondary level.This could help inform the Ministry of Education in providing necessary support for the teachers particularly assessment practices in ESL context as well as in formulating a better assessment policy for schools.